Neuroimmune Basis of Alcoholic Brain Damage - Crews, Fulton T. (Int Rev Neurobiol, 2014)
Alcohol-induced brain damage likely contributes to the dysfunctional poor decisions associated with alcohol dependence. Human alcoholics have a global loss of brain volume that is most severe in the frontal cortex. Neuroimmune gene induction by binge drinking increases neurodegeneration through increased oxidative stress, particularly NADPH oxidase-induced oxidative stress. In addition, HMGB1-TLR4 and innate immune NF-κB target genes are increased leading to persistent and sensitized neuroimmune responses to ethanol and other agents that release HMGB1 or directly stimulate TLR receptors and/or NMDA receptors. Neuroimmune signaling and glutamate excitotoxicity are linked to alcoholic neurodegeneration. Models of adolescent alcohol abuse lead to significant frontal cortical degeneration and show the most severe loss of hippocampal neurogenesis. Adolescence is a period of high risk for ethanol-induced neurodegeneration and alterations in brain structure, gene expression, and maturation of adult phenotypes. Together, these findings support the hypothesis that adolescence is a period of risk for persistent and long-lasting increases in brain neuroimmune gene expression that promote persistent and long-term increases in alcohol consumption, neuroimmune gene induction, and neurodegeneration that we find associated with alcohol use disorders.